Fiqh of Biotechnology: Reinterpreting Qur’anic Verses on the Impurity of Pigs and Its Implications for the Halal Status of Vaccines - Imron, Ali; Muallifah, Anif Yuni (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2025)
The use of pig-derived ingredients in vaccine production, such as trypsin enzyme and gelatin, has sparked controversy among Muslims. This issue stems from the fiqh understanding of the impurity (najāsah) of pigs as stipulated in the Qur’an and Hadith through Qur’anic interpretation. This study aims to reinterpret Qur’anic verses and Hadith on the impurity of pigs within the framework of Fiqh of Biotechnology, a novel approach integrating Islamic jurisprudence and biotechnology. This research employs a qualitative method based on library research, analyzing Qur’anic verses, Hadith, classical and contemporary tafsir, fatwas of Islamic scholars, and relevant biotechnology literature. The findings reveal that there are six Qur’anic verses and at least three Prophetic Hadiths declaring the prohibition of pigs, yet interpretations among scholars vary. From a biotechnological perspective, the trypsin enzyme used in the cell culture stage of vaccine production is entirely removed through filtration and purification processes, rendering it pure. Meanwhile, pig-derived gelatin undergoes significant transformation during vaccine production, which, according to the concept of istihalah, has the potential to alter its legal status to halal. By integrating the fiqh principles of thaharah, najis-mutanajjis, and istihalahwith the purification principles of biotechnology, this study proposes the Fiqh of Biotechnology as a new approach in assessing the halal status of vaccines containing pig-derived ingredients.